EVALUATION OF PUBLIC ROADWAY PARKING MANAGEMENT POLICY AT CIDU MARKET MAKASSAR CITY - Muh. Aqsha Lukmanul Hakim; Sulmiah Sulmiah; Didin Halim (Universitas Negeri Makassar, 2026)
This research aims to find out about the Evaluation of Public Roadside Parking Management Policies at Cidu Market, Makassar City. This research uses a qualitative approach to produce descriptive data. Data collection techniques are carried out through observation, interviews and documentation. The data analysis technique used consists of data reduction, data presentation, and drawing conclusions. The research results show that the Evaluation of Public Roadside Parking Management Policies at Cidu Market, Makassar City is based on the dimensions of effectiveness, efficiency, adequacy, alignment, responsiveness and accuracy. The effectiveness dimension shows that the management policy is not yet optimal, this is because there is still illegal parking on the edge of the public road in Cidu Market, Makassar City. The efficiency dimension shows that although PD Parking has prepared 11 parking attendants, the arrangement of vehicle parking for visitors around the market area is not yet optimal. Cidu, the adequacy dimension shows that there is not enough parking area to accommodate motorized vehicles. The leveling dimension shows that socialization activities regarding notification of public roadside parking management policy regulations in the Pasar Cidu community have not been optimal. The responsiveness dimension shows that the responsiveness of the authorities has not been optimal in dealing with parking problems, besides that there are still people in Cidu Market who are not aware of the existence of regulatory policies. Areas regarding Public Roadside Parking Management. The accuracy dimension shows that the policies that have been issued so far are not on target. Apart from that, regulations regarding Public Roadside Parking Management do not meet the public's expectations in managing parking order and security as well as enforcing sanctions against parking attendants and visitors who violate parking policies on public roads.